Body mass index in midlife and risk of attempted suicide and suicide: prospective study of 1 million UK women. Issue 13 (29th November 2018) - Geulayov, Galit; Ferrey, Anne; Hawton, Keith; Hermon, Carol; Reeves, Gillian K.; Green, Jane; Beral, Valerie; Floud, Sarah; ,
Abstract: Background: High body mass index (BMI) has been associated with lower risks of suicidal behaviour and being underweight with increased risks. However, evidence is inconsistent and sparse, particularly for women. We aim to study this relationship in a large cohort of UK women. Methods: In total 1.2 million women, mean age 56 (s.d. 5) years, without prior suicide attempts or other major illness, recruited in 1996–2001 were followed by record linkage to national hospital admission and death databases. Cox regression yielded relative risks (RRs) and 95% confidence intervals (CIs) for attempted suicide and suicide by BMI, adjusted for baseline lifestyle factors and self-reported treatment for depression or anxiety. Results: After 16 (s.d. 3) years of follow-up, 4930 women attempted suicide and 642 died by suicide. The small proportion (4%) with BMI <20 kg/m 2 were at clearly greater risk of attempted suicide (RR = 1.38, 95% CI 1.23–1.56) and suicide (RR = 2.10, 1.59–2.78) than women of BMI 20–24.9 kg/m 2 ; p < 0.0001 for both comparisons. Small body size at 10 and 20 years old was also associated with increased risks. Half the cohort had BMIs >25 kg/m 2 and, while risks were somewhat lower than for BMI 20–24.9 kg/m 2 (attempted suicide RR = 0.91, 0.86–0.96; p = 0.001; suicide RR = 0.79, 0.67–0.93; p = 0.006), the reductions in risk were not strongly related to level of BMI. Conclusions: Being underweight is associated with a definite increase in the risk of suicidal behaviour, particularly death by suicide. Residual confounding cannot be excluded for the small and inconsistent decreased risk of suicidal behaviour associated with being overweight or obese.